The Effect of Stress and Environment on Nursing Performance - Glendy Ariando Salomon; Zusana A. Sasarari; Anita Lontaan; Femmy Keintjem; Lorrien Grace Runtu (Jurnal Edukasi Ilmiah Kesehatan, 2023)
The development of service organizations in the health sector is a top priority for every consumer to get the best service. Every health institution is competing to provide health facilities and infrastructure to serve consumers as well as possible. This study aimed at the influence of stress and environment on nursing performance. The quantitative research method is a method in this study using a causal research design. Results showed variable work stress: 0.013 and work environment: 0.000. It can be concluded that stress and environment affect nurse performance. High work stress and poor work environment can interfere with nurses' concentration and focus in carrying out their duties and the work environment positively affects nurses' performance. Things that can affect either indirectly or directly the performance of employees and organizations in a company are the work environment.